2022
DOI: 10.3847/1538-4357/ac91c4
|View full text |Cite
|
Sign up to set email alerts
|

The Dust Sublimation Region of the Type 1 AGN NGC 4151 at a Hundred Microarcsecond Scale as Resolved by the CHARA Array Interferometer

Abstract: The nuclear region of Type 1 active galactic nuclei (AGNs) has only been partially resolved so far in the near-infrared (IR), where we expect to see the dust sublimation region and the nucleus directly without obscuration. Here, we present the near-IR interferometric observation of the brightest Type 1 AGN NGC 4151 at long baselines of ∼250 m using the CHARA Array, reaching structures at hundred microarcsecond scales. The squared visibilities decrease down to as low as ∼0.25, definitely showing that the struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Appendix A Table A1. Observed values of nonpolarized continuum and nonpolarized and polarized broad line flux for Mrk 335, Mrk 509 and Mrk 817 : (1) date of observations (dd/mm/yyyy), (2) the same in Julian form JD-2450000, (3) continuum flux in mJy, (4) the Stokes Q parameters of the continuum flux in %, (5) the Stokes U parameters of the continuum flux in %, (6) broad Hα line flux with subtracted continuum, in mJy, (7) the Stokes Q parameters of the line flux with subtracted continuum, in %, (8) the Stokes U parameters of the line flux with subtracted continuum, in %, (9) polarized broad Hα line flux with subtracted continuum, in mJy. For Mrk 817, the upper values of I line , Q line , U line and I p line are for the "blue" line profile wing and the bottom values are for the "red" wing.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Appendix A Table A1. Observed values of nonpolarized continuum and nonpolarized and polarized broad line flux for Mrk 335, Mrk 509 and Mrk 817 : (1) date of observations (dd/mm/yyyy), (2) the same in Julian form JD-2450000, (3) continuum flux in mJy, (4) the Stokes Q parameters of the continuum flux in %, (5) the Stokes U parameters of the continuum flux in %, (6) broad Hα line flux with subtracted continuum, in mJy, (7) the Stokes Q parameters of the line flux with subtracted continuum, in %, (8) the Stokes U parameters of the line flux with subtracted continuum, in %, (9) polarized broad Hα line flux with subtracted continuum, in mJy. For Mrk 817, the upper values of I line , Q line , U line and I p line are for the "blue" line profile wing and the bottom values are for the "red" wing.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…its location and chemical composition determine the accretion properties of the AGN. Thanks to high-angular-resolution observations of local active galaxies in the infrared (IR) (e.g., [4][5][6][7][8]) and molecular lines (e.g., [9,10]) now it becomes possible to obtain direct images of the dusty region, while in the optical range, this structure is still unresolvable. The development of observational capabilities made it possible to determine the geometry of the dusty region, which turned out to be different from the toroidal (see [11] for a review), and also to move from the simple models of a clumpy [12] and smooth-distributed [13] dusty "torus" to more complex ones ( [7,14,15] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Appendix A Table A1. Observed values of nonpolarized continuum and nonpolarized and polarized broad line flux for Mrk 335, Mrk 509 and Mrk 817 : (1) date of observations (dd/mm/yyyy), (2) the same in Julian form JD-2450000, (3) continuum flux in mJy, (4) the Stokes Q parameters of the continuum flux in %, (5) the Stokes U parameters of the continuum flux in %, (6) broad Hα line flux with subtracted continuum, in mJy, (7) the Stokes Q parameters of the line flux with subtracted continuum, in %, (8) the Stokes U parameters of the line flux with subtracted continuum, in %, (9) polarized broad Hα line flux with subtracted continuum, in mJy. For Mrk 817, the upper values of I line , Q line , U line and I p line are for the "blue" line profile wing and the bottom values are for the "red" wing.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…its location and chemical composition determine the accretion properties of the AGN. Thanks to highangular-resolution observations of local active galaxies in the infrared (IR) (e.g., [4][5][6][7][8]) and molecular lines (e.g., [9,10]) now it becomes possible to obtain direct images of the dusty region, while in the optical range, this structure is still unresolvable. The development of observational capabilities made it possible to determine the geometry of the dusty region, which turned out to be different from the toroidal (see [11] for a review), and also to move from the simple models of a clumpy [12] and smooth-distributed [13] dusty "torus" to more complex ones ( [7,14,15] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The inner disc-like component is likely due to the gaseous response to the primary bar Asif et al 2005). Inside this inner gaseous feature is an outflowing ionised gas from the AGN (Kishimoto et al 2022). Wang et al (2010) reported that the galaxy might have experienced an Eddington-rate outburst ∼ 10,000 yrs ago.…”
Section: Appendix A: Notes On Selected Individual Galaxiesmentioning
confidence: 99%